High-crack-resistance self-leveling concrete for prefabricated building and preparation method of high-crack-resistance self-leveling concrete

By adding polypropylene fibers and polycarboxylic acid-based high-efficiency water reducing agents to self-leveling concrete, the problem of microcracks and poor fluidity in the hardening process of self-leveling concrete is solved, and the high crack resistance and fluidity are improved, and the stability and durability of the structure are improved.

CN119822738APending Publication Date: 2025-04-15CHINA MCC17 GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510053093.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing self-leveling concrete is prone to microcracks during hardening, especially in environments with large drying and temperature differences, and has poor fluidity during construction, resulting in a decrease in strength and durability.

Method used

By adding polypropylene fibers and polycarboxylic acid-based high-efficiency water reducing agents to the concrete, the material ratio and preparation process are optimized, and an effective stress dispersion network is formed and fluidity is improved.

Benefits of technology

It significantly improves the crack resistance and flowability of concrete, reduces the expansion of microcracks, improves the stability and durability of the structure, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822738A_ABST
    Figure CN119822738A_ABST
Patent Text Reader

Abstract

The invention discloses high-crack-resistance self-leveling concrete for prefabricated buildings and a preparation method of the high-crack-resistance self-leveling concrete. The concrete is prepared from components in percentage by mass as follows: 25%-40% of ordinary Portland cement, 30%-50% of fine aggregate, 5%-15% of fly ash, 5%-15% of mineral powder, 0.5%-2% of a polycarboxylate superplasticizer, 0.1%-1% of polypropylene fiber and 10%-15% of water. The invention relates to the technical field of high-crack-resistance self-leveling concrete. According to the high-crack-resistance self-leveling concrete for the prefabricated building and the preparation method thereof, by adding the polypropylene fibers, the crack resistance of the concrete is remarkably improved, the length and the diameter of the polypropylene fibers are optimized, an effective stress dispersion network can be formed in the concrete, microcrack propagation is reduced, and the crack resistance of the concrete is improved. And by using the polycarboxylate superplasticizer, the flowability of the concrete, the high water-reducing rate of the superplasticizer and good dispersing performance are remarkably improved, so that the concrete can still keep good flowability at a relatively low water-binder ratio, and is easy to construct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of highly crack-resistant self-leveling concrete, in particular to highly crack-resistant self-leveling concrete for assembled buildings and a preparation method thereof. Background Art

[0002] High crack resistance self-leveling concrete is a special concrete material with self-leveling properties and excellent crack resistance. This concrete can automatically flow, self-level and fill the formwork after pouring without manual construction and vibration.

[0003] However, the existing self-leveling concrete is prone to microcracks during the hardening process, especially in a dry environment with a large temperature difference, the crack problem is more serious, the cracks not only affect the appearance of the components, but also reduce their structural stability and durability. At the same time, the existing self-leveling concrete has poor fluidity during the construction process, and a higher water-cement ratio is required to ensure fluidity, resulting in a decrease in the strength and durability of the concrete. Therefore, in view of the above shortcomings, the present invention makes the following improvements. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a highly crack-resistant self-leveling concrete for prefabricated buildings and a preparation method thereof, which solves the problems mentioned in the background technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a highly crack-resistant self-leveling concrete for prefabricated buildings, the concrete consisting of the following components in percentage by mass: 25-40% ordinary Portland cement, 30-50% fine aggregate, 5-15% fly ash, 5-15% mineral powder, 0.5-2% polycarboxylic acid-based high-efficiency water reducing agent, 0.1-1% polypropylene fiber, and 10-15% water.

[0006] Preferably, the particle size of the fine aggregate is in the range of 0.1-2.0 mm, and the mud content of the fine aggregate does not exceed 1%.

[0007] Preferably, the polypropylene fiber has a length of 6-12 mm, a diameter of 10-30 μm, and a tensile strength of not less than 300 MPa.

[0008] Preferably, the water reduction rate of the polycarboxylic acid-based high-efficiency water reducer is not less than 25%, and the initial water reduction rate of the water reducer is not less than 20%, and the water reduction rate after 1 hour is not less than 15%.

[0009] The present invention also discloses a method for preparing highly crack-resistant self-leveling concrete for assembled buildings, which specifically comprises the following steps:

[0010] S1. Weigh each component according to mass percentage;

[0011] S2, adding ordinary Portland cement, fine aggregate, fly ash and mineral powder into a forced mixer, stirring at a speed of 30-60 rpm for 2-5 minutes until the mixture is uniform, to obtain a dry mix;

[0012] S3, dissolving a polycarboxylic acid-based high-efficiency water reducer in 20-30% of the total water to prepare a water reducer solution, adding the remaining water to the dry mix, and stirring at a speed of 30-60 rpm for 3-8 minutes until a uniform wet mix is ​​formed;

[0013] S4. Slowly add the water reducing agent solution to the wet mix and continue stirring at 30-60 rpm for 2-4 minutes until fully mixed;

[0014] S5. Add polypropylene fibers to the above mixture and stir at a speed of 30-60 rpm for 2-4 minutes until the fibers are evenly distributed, thereby finally obtaining a highly crack-resistant self-leveling concrete.

[0015] Preferably, the stirring time in step S2 is 3 minutes, the stirring time in step S3 is 5 minutes, the stirring time in step S4 is 3 minutes, and the stirring time in step S5 is 3 minutes.

[0016] Preferably, the stirring blades of the forced mixer in step S2 are spiral-shaped to ensure uniform mixing.

[0017] Preferably, in step S3, the water reducing agent solution is first added into the mixer, and then the remaining water is added, and then added into the dry mix and stirred evenly.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The addition of polypropylene fibers significantly improves the crack resistance of concrete. The length and diameter of polypropylene fibers are optimized to form an effective stress dispersion network inside the concrete, reduce the expansion of microcracks, and thus improve the stability and durability of the overall structure. The use of polycarboxylic acid-based high-efficiency water reducer significantly improves the fluidity of concrete. The high water reduction rate and good dispersion performance of the water reducer enable the concrete to maintain good fluidity at a lower water-cement ratio, making it easy to construct.

[0020] After the components are cast with the high crack-resistant self-leveling concrete prepared by the present invention, the surface flatness error of the components does not exceed ±2mm, and there are no obvious cracks, bubbles and voids, which not only improves the aesthetics of the components, but also ensures the safety and functionality of the structure. By optimizing the material ratio and the preparation process, the concrete of the present invention reduces the production cost and improves the market competitiveness while ensuring high performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the process steps of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1

[0024] A method for preparing highly crack-resistant self-leveling concrete for prefabricated buildings, specifically comprising the following steps:

[0025] S1. Weigh each component according to mass percentage;

[0026] S2, adding 0.5% ordinary Portland cement, 40% fine aggregate, 15% fly ash and 5% mineral powder into a forced mixer, stirring at a speed of 50 rpm for 3 minutes until the mixture is uniformly mixed to obtain a dry mix;

[0027] S3, dissolving 0.5% polycarboxylic acid-based high-efficiency water reducer in 25% of the total water to prepare a water reducer solution, adding the remaining water to the dry mix, and stirring at a speed of 30 rpm for 5 minutes until a uniform wet mix is ​​formed;

[0028] S4. Slowly add the water reducing agent solution to the wet mixture and continue stirring at 30 rpm for 3 minutes until fully mixed;

[0029] S5. Add 0.5% polypropylene fiber to the above mixture and stir at a speed of 30 rpm for 3 minutes until the fiber is evenly distributed, thereby finally obtaining a highly crack-resistant self-leveling concrete.

[0030] Embodiment 2

[0031] Compared with the first embodiment, the specific differences of this embodiment are: ordinary Portland cement is 35%, fine aggregate is 43%, fly ash is 5%, mineral powder is 5%, polycarboxylic acid-based high-efficiency water reducing agent is 1%, polypropylene fiber is 1%, and water is 10%.

[0032] Embodiment 3

[0033] Compared with the first embodiment, the specific differences of this embodiment are: ordinary Portland cement is 35%, fine aggregate is 30%, fly ash is 10%, mineral powder is 10%, polycarboxylic acid-based high-efficiency water reducing agent is 1.5%, polypropylene fiber is 0.5%, and water is 13%.

[0034] Comparative test

[0035] The test objects include the concrete of the present invention (named "the invention concrete") and an existing ordinary self-leveling concrete (named "the existing concrete"). The main parameters of the test include compressive strength, flexural strength, shrinkage rate, initial setting time, surface flatness and crack resistance, specifically including:

[0036] Test Materials:

[0037] Ordinary Portland cement: P.O42.5;

[0038] Fine aggregate: river sand, particle size range 0.2-1.5mm, mud content not exceeding 1%;

[0039] Fly ash: Class I fly ash;

[0040] Mineral powder: S95 grade mineral powder;

[0041] Polycarboxylic acid-based high-efficiency water reducing agent: water reduction rate not less than 25%, initial water reduction rate not less than 20%, water reduction rate after 1 hour not less than 15%;

[0042] Polypropylene fiber: 8 mm in length, 20 μm in diameter, and 350 MPa in tensile strength;

[0043] Water: purified water;

[0044] Test equipment: forced mixer, compressive strength tester, flexural strength tester, shrinkage tester, initial setting time tester, surface flatness measuring instrument and crack observation instrument;

[0045] Test steps:

[0046] Weigh the materials:

[0047] Invention concrete: 35% ordinary Portland cement, 30% fine aggregate, 10% fly ash, 10% mineral powder, 1.5% polycarboxylic acid series high-efficiency water reducing agent, 0.5% polypropylene fiber, 13% water;

[0048] Existing concrete: 40% ordinary Portland cement, 45% fine aggregate, 15% water;

[0049] Prepare a dry mix: add ordinary Portland cement, fine aggregate, fly ash and mineral powder into a forced mixer, and stir at a speed of 40 rpm for 3 minutes until the mixture is uniform to obtain a dry mix;

[0050] Prepare wet mix: dissolve the polycarboxylic acid-based high-efficiency water reducer in 25% of the total water to prepare a water reducer solution, add the remaining water to the dry mix, stir at 40 rpm for 5 minutes until a uniform wet mix is ​​formed, slowly add the water reducer solution to the wet mix, and continue stirring at 40 rpm for 3 minutes until it is fully mixed;

[0051] Adding fibers: Add polypropylene fibers to the above mixture and stir at a speed of 40 rpm for 3 minutes until the fibers are evenly distributed, thereby finally obtaining a highly crack-resistant self-leveling concrete;

[0052] Pouring and curing: Pour the prepared concrete into standard test molds, vibrate to compact, scrape the surface flat, and cure the specimens under standard curing conditions, with a temperature of 20℃±2℃ and a relative humidity of more than 95%;

[0053] Performance Testing:

[0054] Compressive strength: compressive strength tests were conducted at 7 days and 28 days;

[0055] Flexural strength: Flexural strength tests were conducted at 7 days and 28 days respectively;

[0056] Shrinkage: Shrinkage test was conducted at 28 days;

[0057] Initial setting time: initial setting time test is carried out after pouring;

[0058] Surface smoothness: Surface smoothness test was conducted at 28 days;

[0059] Crack resistance: Carry out crack resistance test at 28 days, observe and record the number and width of cracks;

[0060] Table data:

[0061]

[0062]

[0063] It can be seen from the data in the table that the high crack resistance self-leveling concrete of the present invention is superior to the existing ordinary self-leveling concrete in multiple performance indicators. The specific analysis is as follows:

[0064] Compressive strength: At 7 days, the compressive strength of the invented concrete was 35MPa, while the existing concrete was only 28MPa, an increase of 25%;

[0065] At 28 days, the compressive strength of the invented concrete was 42 MPa, while that of the existing concrete was 36 MPa, an increase of 16.7%;

[0066] This indicates that the invented concrete has higher compressive strength at both early and later stages, mainly due to the fact that the addition of fly ash and mineral powder improves the microstructure of concrete and increases its density;

[0067] Flexural strength: At 7 days, the flexural strength of the invented concrete was 6.5MPa, while that of the existing concrete was 5.0MPa, an increase of 30%;

[0068] At 28 days, the flexural strength of the invented concrete was 8.0 MPa, while that of the existing concrete was 6.5 MPa, an increase of 23.1%;

[0069] This indicates that the invented concrete has higher flexural strength both in the early and later stages, thanks to the addition of polypropylene fibers, which forms an effective stress dispersion network and enhances the toughness of the concrete;

[0070] Shrinkage rate: At 28 days, the shrinkage rate of the invented concrete was 0.03%, while that of the existing concrete was 0.08%, a decrease of 62.5%;

[0071] Low shrinkage means that the invented concrete generates less shrinkage stress during the drying process, which reduces the risk of cracking and improves the stability and durability of the components;

[0072] Initial setting time: The initial setting time of the invented concrete is 24 hours, while that of the existing concrete is 36 hours, which is shortened by 33.3%;

[0073] Shorter initial setting time is conducive to speeding up construction progress and improving construction efficiency, especially in projects with tight construction schedules.

[0074] Surface flatness: The surface flatness error of the invented concrete is ±1.5mm, while that of the existing concrete is ±3.0mm, which is a 50% reduction.

[0075] High surface flatness not only improves the aesthetics of the component, but also ensures the safety and functionality of the structure, reducing the cost and time of subsequent processing;

[0076] In summary, the high crack-resistant self-leveling concrete of the present invention shows significant superiority in compressive strength, flexural strength, shrinkage rate, initial setting time, surface flatness and crack resistance. The improvement in performance not only solves the deficiencies in the prior art, but also provides a more reliable and efficient material selection for prefabricated buildings, and has important practical application value and market prospects.

[0077] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly crack-resistant self-leveling concrete for assembled buildings, characterized in that: The concrete is composed of the following components in percentage by mass: 25-40% of ordinary Portland cement, 30-50% of fine aggregate, 5-15% of fly ash, 5-15% of mineral powder, 0.5-2% of polycarboxylic acid series high-efficiency water reducing agent, 0.1-1% of polypropylene fiber, and 10-15% of water.

2. The highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 1, characterized in that: The particle size of the fine aggregate is in the range of 0.1-2.0 mm, and the mud content of the fine aggregate does not exceed 1%.

3. The highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 2, characterized in that: The polypropylene fiber has a length of 6-12 mm, a diameter of 10-30 μm, and a tensile strength of not less than 300 MPa.

4. The highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 3 is characterized in that: The water reduction rate of the polycarboxylic acid-based high-efficiency water reducing agent is not less than 25%, and the initial water reduction rate of the water reducing agent is not less than 20%, and the water reduction rate after 1 hour is not less than 15%.

5. A method for preparing highly crack-resistant self-leveling concrete for prefabricated buildings, characterized in that: The highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 4 specifically comprises the following steps: S1. Weigh each component according to mass percentage; S2, adding ordinary Portland cement, fine aggregate, fly ash and mineral powder into a forced mixer, stirring at a speed of 30-60 rpm for 2-5 minutes until the mixture is uniform, to obtain a dry mix; S3, dissolving a polycarboxylic acid-based high-efficiency water reducer in 20-30% of the total water to prepare a water reducer solution, adding the remaining water to the dry mix, and stirring at a speed of 30-60 rpm for 3-8 minutes until a uniform wet mix is ​​formed; S4. Slowly add the water reducing agent solution to the wet mix and continue stirring at 30-60 rpm for 2-4 minutes until fully mixed; S5. Add polypropylene fibers to the above mixture and stir at a speed of 30-60 rpm for 2-4 minutes until the fibers are evenly distributed, thereby finally obtaining a highly crack-resistant self-leveling concrete.

6. The method for preparing a highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 1, characterized in that: The stirring time in step S2 is 3 minutes, the stirring time in step S3 is 5 minutes, the stirring time in step S4 is 3 minutes, and the stirring time in step S5 is 3 minutes.

7. The method for preparing a highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 1, characterized in that: The stirring blades of the forced mixer in step S2 are spiral-shaped to ensure uniform mixing.

8. The method for preparing a highly crack-resistant self-leveling concrete for prefabricated buildings according to claim 1, characterized in that: In step S3, the water reducing agent solution is first added into the mixer, and then the remaining water is added, and then added into the dry mix and stirred evenly.